Field synergy principle analysis on convective heat transfer in porous medium with uniform heat generation for thermally developing flow - Chen, G. M. (2013)
The field synergy analysis for forced convective heat transfer in porous medium between two parallel plates is augmented from the earlier study on developed flow to the present thermally developing flow. The temperature variations along the axial and transverse directions for both adiabatic and isoflux boundary conditions are studied. Green’s function solution integrated with the extended weighted residuals method is adopted in this study to first obtain the temperature profile. The variation of intersection angle in the context of field synergy analysis is discussed in relations to the Nusselt number, boundary conditions and the shape factor.